A comparison of char fuel properties derived from dry and wet torrefaction of oil palm leaf and its techno-economic feasibility - Lokmit C. (2023)
In this study, the chars were derived through dry and wet torrefaction (DT and WT) of oil palm leaf (OPL), and techno-economic feasibility for char production was evaluated. DT was performed at 200 to 300 °C for 30 min under CO2 atmosphere. WT was performed at 180 to 220 °C for 30 min over process water (PW) reuse. Fuel properties of the DT-char and WT-char products, including mass yield, physiochemical characteristics, fuel properties, thermal stability, surface chemical functional groups, and surface structure were investigated. The study results indicated that DT affected OPL characteristics rather than WT, where the char with outstanding fuel properties was derived through DT. WT affected the fuel properties of OPL marginally. OPL chars with the highest HHV (28.67 MJ/kg), HHV improvement (0.48) and energy yield (131.78 %) could be derived via the DT. The O/C and H/C ratios of the DT-char were reduced and similar to those of lignite coal. PW reuse in WT slightly affected the char fuel properties, thus it is the outstanding method of PW utilization. Techno-economic feasibility analysis results determined that DT is the profitable process for converting OPL to char fuel, and its simple payback period is 14.13 years. These results recommended that DT constitutes a dominant technology for producing char fuel from OPL.